Malignant melanoma of penis: case report and literature review - Rhoden, Ernani Luís (2022)
Tumours of the penis are rare, and responsible for less 1% of the male neoplasias. More uncommon is the penile primary malignant melanoma. The prognosis of this neoplasia is bad and need aggressive mana gement. We report a case of prímary malignant melanoma of the glans from the penis and review the literature.